First Detection of the Jingmen Tick Virus in Amblyomma testudinarium Ticks from the Kanto Region, Japan - Matsumura, Ryo; Kobayashi, Daisuke; Itoyama, Kyo; Isawa, Haruhiko (Japanese Journal of Infectious Diseases, 2024)
In 2010, Jingmen tick virus (JMTV) was discovered in ticks in China and has been shown to be distributed in several regions worldwide. Recently, cases of JMTV infection in humans have been reported in China and Kosovo, and have attracted much attention as an emerging tick-borne disease. In this study, we detected the JMTV genome in Amblyomma testudinarium ticks collected in Kanagawa Prefecture, Japan, during tick-borne virus surveillance conducted in the Kanto Region. Phylogenetic analysis revealed that the new JMTV strain was closely related to previous strains detected in Japan. This suggests that JMTV may have been maintained during an independent natural transmission cycle in Japan. In addition, unlike other countries and regions, all JMTV strains in Japan were detected only in A. testudinarium ticks, suggesting that this tick species is the primary JMTV vector in Japan. This is the first report of JMTV in the Kanto Region. Further studies are required to elucidate the potential risk of infection with this tick-borne virus in Japan. In particular, the prevalence of JMTV in wild animals should be examined to clarify its geographical distribution, host range, and transmission cycle.